2006
DOI: 10.1063/1.2387888
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Cr- and Al-based metals for the reflector and Ohmic contact on n-GaN in GaN flip-chip light-emitting diodes

Abstract: This letter investigates three composite metals used as a reflector and Ohmic contact on n-GaN to simplify the process in a flip-chip light-emitting diode (FCLED). The investigated composite metals were Ti∕Al∕Ti∕Au, Cr∕Al∕Cr∕Au, and Cr∕Ti∕Au. The specific contact resistivities of the Ti∕Al∕Ti∕Au, Cr∕Al∕Cr∕Au, and Cr∕Ti∕Au Ohmic contacts on n-GaN were changed from 1.4×10−4, 1.7×10−4, and 1.9×10−4Ωcm2 to 1.3×10−4, 1.1×10−4, and 3.3×10−5Ωcm2, respectively, after 500h of thermal stress. The corresponding operating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…There are not many reports in the literature describing ohmic contacts to n-GaN without post-deposition annealing or annealing at relatively low temperatures. In addition, such works are only concerned with highly doped semiconductors [ 33 , 34 ]. In this work, annealing at 850 °C in a nitrogen atmosphere resulted in an ohmic character of the contact ( Figure 4 b).…”
Section: Resultsmentioning
confidence: 99%
“…There are not many reports in the literature describing ohmic contacts to n-GaN without post-deposition annealing or annealing at relatively low temperatures. In addition, such works are only concerned with highly doped semiconductors [ 33 , 34 ]. In this work, annealing at 850 °C in a nitrogen atmosphere resulted in an ohmic character of the contact ( Figure 4 b).…”
Section: Resultsmentioning
confidence: 99%
“…With the use of molecular beam epitaxy (MBE), we have demonstrated the monolithic integration of nearly defect-free GaN/Al/GaN tunnel junction LED heterostructures. Unique to the Al-based tunnel junction is that the Al layer with appropriate thickness can serve as a mirror to reflect light emitted from the active region, 29,30 given its high reflectivity (∼90%) in the visible and UV spectral range, which is in direct contrast to the light absorption induced by polarization engineered tunnel junctions in previous reports. 6,9 We have further shown that the incorporation of such tunnel junctions in InGaN/GaN dot-in-a-wire LEDs can lead to significantly improved light output power and lower operation voltage, compared to identical nanowire devices without the use of tunnel junctions or with the incorporation of n ++ -GaN/p ++ -GaN tunnel junctions.…”
mentioning
confidence: 99%
“…However, there is still a need to improve their light extraction efficiency, as well as their internal quantum efficiency. Many LED configurations, such as flip-chip LEDs (FCLEDs), [1][2][3][4] resonant-cavity LEDs (RCLEDs), 5 and vertical LEDs (VLEDs), [6][7][8][9][10] have been designed to improve the light extraction efficiency by increasing the active area or by eliminating the unnecessary regions that lower their efficiency. Among them, VLEDs have been considered as the ultimate structure to maximize the extraction efficiency based on current fabrication technology.…”
mentioning
confidence: 99%